Heavy work investment from the perspective of cultural factors and outcomes by types of investors - Rodica Cristina Butnaru; Alexandru Anichiti; Gina Ionela Butnaru; Alina Petronela Haller (Amfiteatru Economic Journal, 2020)
This paper aims to analyse the concept of Heavy Work Investment (HWI) by studying the factors determining this phenomenon, as well as its outcomes (both negative and positive). According to the European Directive of 1993, Heavy Work Investment occurs when an individual works more than 48 hours per week. The aim of this paper is to study the factors influencing the occurrence of the phenomenon of Heavy Work Investment from the perspective of time invested, using the multiple regression model, as well as the outcomes of Heavy Work Investment, using the structural equation model (SEM). The study used the data of the countries included in the International Social Survey Programme (ISSP), (37 countries and a total of 18,274 respondents) on employment status, the number of actual working hours, job and demographic characteristics. The results confirm the important impact of the cross-cultural differences on HWI behaviour as well as the outcomes of Heavy Work Investment according to the type of investor (dispositional / situational).
Keywords: J22; J23; O15; 330; Heavy Work Investment; working hours; cross-cultural differences; dispositional investors; situational investors